Agropolitan Tourism Village Strategies Based on SWOT Analysis - Ida Nuraida; Bambang Sugiharto; Yuwana Marjuka (Master of Management, School of Business and Management, Petra Christian University, 2023)
Despite its rich potentials, agritourism in West Bandung regency has been stuck in the status quo and needs new ideas. The farmers are struggling on their own with minimal support from the government, the uniqueness of their local culture has never been exposed, and the infrastructure is poor. The concept of ‘agropolitan’ is one of the best possibilities to implement. The aim of this research is to create an agropolitan strategy that that is workable based on the analysis of strengths, weaknesses, opportunities, and threats (SWOT analysis). The research objects were 15 micro-scale community-based agritourism farmers and 5 agritourism MSMEs. This research used qualitative methodology with in-depth interviews and field observations. The research came up with a strategy that requires the materialization of the following items: Agropolitan promotion centers will prepare a central tourism information system, one stop shopping packages, parking lots, and tour transportation. Agropolitan stakeholders will need to improve service quality, increase collaboration and provide employment. Whereas the local governments will have to provide support for facilities, infrastructure, regulations, signage and gates. All this will be able to increase promotion and empower MSMEs. If implemented, this will be able to revitalize agritourism much better.